Act or Wait and See the Challenges: Artificial Intelligence for Analysing Schizophrenia Syndromes in Social Media - Gulati, Akash; Arora, Sugandh; Longani, Kirti Dang (Procedia of Social Sciences and Humanities, 2024)
Schizophrenia is a complicated and crippling mental illness that makes it hard to find and treat early on. With the rise of social media, there is a lot of information available to help people learn more about mental health issues, such as schizophrenia syndromes. It might be possible to find possible signs of schizophrenia and improve the diagnostic process by using artificial intelligence (AI) techniques to look at social media data. The frequent use of social media can be indicative of linguistic impairments or alterations brought on by symptoms shared by a variety of mental health illnesses. Over the past 25 years, the detection of these linguistic cues has been studied; however, with the pandemic, interest and methodological advancement have increased dramatically. It is possible that within the next ten years, trustworthy techniques for utilising social media data to forecast mental health status will emerge. This could have an impact on public health policy and clinical practise, especially when it comes to early intervention in mental health treatment.